Configurable topological beam splitting via antichiral gyromagnetic photonic crystal - Jianfeng Chen; Zhi-Yuan Li (Opto-Electronic Science, 2022)
Antichiral gyromagnetic photonic crystal (GPC) in a honeycomb lattice with the two interpenetrating triangular sublattices A and B magnetically biased in opposite directions can realize antichiral one-way edge states propagating along the same direction at its two parallel edges. Here, we report the construction and observation of topological beam splitting with the easily adjustable right-to-left ratio in an antichiral GPC. The splitter is compact and configurable, has high transmission efficiency, and allows for multi-channel utilization, crosstalk-proof, and robust against defects and obstacles. This magnificent performance is attributed to the peculiar property that antichiral one-way edge states exist only at zigzag edge but not at armchair edge of antichiral GPC. When we combine two rectangular antichiral GPCs holding left- and right-propagating antichiral one-way edge states respectively, bidirectionally radiating one-way edge states at two parallel zigzag edges can be achieved. Our observations can enrich the understanding of fundamental physics and expand topological photonic applications.